ANALISA WEBSITE PRODI SISTEM INFORMASI UNSIKA BERDASARKAN PRINSIP DAN PARADIGMA INTERAKSI MANUSIA DAN KOMPUTER - Ahzka Nabbilah Tuzzahrah; Apriade Voutama; Azhari Ali Ridha (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
The Unsika Information Systems Study Program Website is a place where Unsika Information Systems students can access information about lectures. The purpose of analyzing the Unsika Information Systems Study Program Website is to be able to find out the relationship between system functions based on the principles and paradigm of Human and Computer Interaction (HCI). In the Website interface design analysis, the author uses the heuristic evaluation method with the aspects being evaluated are human, technology, usability, and ergonomisc aspects. The results of the analysis prove that the Unsika Information Systems Study Program Website has fulfilled the aspects of Human and Computer Interaction where the goal of IMK itself is to make it easy for users to manage the system and be able to generate the required feedback.